Scientific Linguodidactic Dialogue in Era of Globalization (towards the 50th Anniversary of International Association of Russian Language and Literature Teachers) - S. A. Vishnyakova (Научный диалог, 2018)
It is reported about the international conference held at the philological faculty of Moscow State University on November 16-17, 2018, devoted to the Russian language and literature in the context of globalization. It is told that in the conference mode scientists from different countries shared their experience at intercultural communication, professional communication, methods of teaching Russian as a foreign language, linguistic and didactic description of the Russian language.